Exogenous vs. endogenous governance in innovation communities: Effects on motivation, conflict and justice - An experimental investigation - Niclas Störmer; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2014)
In this study we examine the effects of exogenous vs. endogenous governance rules on a virtual community handling an innovative task. Specifically we investigate the relationship between the two modes (exogenous vs. endogenous) and factors such as motivation, conflict and justice. We conducted an experiment with 70 students, divided into teams of five. We manipulated procedural legitimacy by allowing one group to choose a set of rules and giving the other group the same rules exogenously. Our study indicates, that letting a team choose its own governance rules leads to increasing level of conflict negatively impacting motivation.
Keywords: 330; Governance; Collaborative Innovation Communities